Physiological factors associated with middle distance running performance - Brandon, L. J. (Sports Medicine, 1995)
Middle distance runners are not restricted to a set of defined physiological attributes for performances. Various mixes of aerobic and anaerobic variables produce champions. However, those same champions are usually higher than normal in both aerobic and anaerobic capacities, which contributes to their superiority. The major factor that distinguishes elite from lesser performers is the economy of movement exhibited at racing speeds, a phenomenon which is not reflected at slower speeds. The technique of running fast has a lot to do with middle distance running success. Running economy is the determinant of success among runners with very similar VO2max values. Contributions from running economy are different for middle distance runners than for distance performers. They can run at higher velocities with a better economy than at lower velocities.